Tubuh Dan Jiwa Manusia Dalam Perspektif Filsafat Rene Descartes - Luh Putu Cita Ardiyani; Kadek Suciani; Krisna Sukma Yogiswari (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2021)
Ren Descartes is often referred to as the father of modern philosophy. Descartes was also a philosopher whose philosophical teachings were very popular because of his unwavering view of the highest truth in human reason or reason. Descartes was not satisfied with the philosophy of his era which was considered less systematic and lacked a scientific method, for him a suitable method for updating philosophy was methodical doubt, so that through this methodical doubt or skeptical method Descartes was able to contribute new knowledge in the history of the development of Western philosophy. Keyword: Skeptisisme method, knowledge